Uma abordagem do modelo padrão da física de partículas acessível a alunos do ensino médio - Maia, Marcilon Chaves (2011)
This work has, as a main purpose or focal point, to explore a story: "Quantumland, the Republic of particles," a fiction created by the author, which also presents historical aspects, concepts and ideas of elementary particles physics aiming to offer a funny way to introduce the so-called Standard Model of particle physics to high school students. From the story presentation we try to show some essential features of the atomic theory, with the discoveries and concepts that led to our nowadays knowledge about elementary particles, and also to show some considerations about the status of the theory in modern physics. Guided by this core theme we developed two questionnaires that were applied to two high school classes in Fortaleza and in two different moments: one before and one after the story introduction. These questionnaires tried to test the students background concerning the most basic or essential contents involved in the theme. The work showed that the so-called Standard Model of Particle Physics, as the author had already experienced in his job as a physics teacher (and proved by means of questionnaires mentioned) is not a familiar theme for most high school students. Some students (the most well-informed) have at most "heard" something about quarks, spin, quantum energy, virtual particles or other terms of the typical jargon of physics, but most of them do not even have an adequate grasp of what was known as a elementary particle. As one of the conditions of Ausubel's Meaningful Reception theory that learning must be potentially significant or has to be logical and psychologically meaningful, we thought of a simple way, without appeals to mathematical formulae that could facilitate the student learning of the ideas and guide him to a constructive curiosity.